2015
DOI: 10.1007/s12026-015-8759-5
|View full text |Cite
|
Sign up to set email alerts
|

An antimicrobial peptide with angiogenic properties, AG-30/5C, activates human mast cells through the MAPK and NF-κB pathways

Abstract: Apart from their direct antimicrobial activities against invading pathogens, antimicrobial peptides exhibit additional protective functions that have led to their being named host defense peptides (HDPs). These functions include the stimulation of the production of cytokines/chemokines, the promotion of chemotaxis and cell proliferation and the induction of angiogenesis and wound healing. AG-30/5C is a novel angiogenic HDP that in addition to its antimicrobial activity also activates fibroblasts and endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Likewise, the in vivo anti-bacterial effects of the designer Chex-Arg20 proline-arginine-rich peptide are more extensive when embedded in a nanofiber formulation than after intramuscular administration using only one-tenth of the active pharmaceutical ingredient [49]. The various cutaneous and wound healing activities are likely linked to the ability of HDP to activate mast cells and enhance the production of cytokines (GM-CSF, TNF-α) and chemokines (IL-8-MCPs and MIPs) at inflammation and injury sites [50]. Along these lines, a polyelectrolyte multilayer film based on polyarginine and hyaluronic acid has a remarkable anti-microbial activity in a film format against Staphylococcus aureus and as well as inhibits the production of inflammatory cytokines released by human primary macrophages [51].…”
Section: Wide Spectrum Of Immune Stimulatory Peptidesmentioning
confidence: 99%
“…Likewise, the in vivo anti-bacterial effects of the designer Chex-Arg20 proline-arginine-rich peptide are more extensive when embedded in a nanofiber formulation than after intramuscular administration using only one-tenth of the active pharmaceutical ingredient [49]. The various cutaneous and wound healing activities are likely linked to the ability of HDP to activate mast cells and enhance the production of cytokines (GM-CSF, TNF-α) and chemokines (IL-8-MCPs and MIPs) at inflammation and injury sites [50]. Along these lines, a polyelectrolyte multilayer film based on polyarginine and hyaluronic acid has a remarkable anti-microbial activity in a film format against Staphylococcus aureus and as well as inhibits the production of inflammatory cytokines released by human primary macrophages [51].…”
Section: Wide Spectrum Of Immune Stimulatory Peptidesmentioning
confidence: 99%
“…AG-30/5C is a synthetic angiogenic HDP that promotes new blood vessel formation, induces human keratinocyte proliferation, effectively clears microbial infection, and induces wound healing in mice (17). The ability of AG-30/5C to harness MC's immunomodulatory property likely contributes to its host defense, but the mechanism via which it activates MC remains unknown (19). The data presented in this article clearly demonstrate that AG-30/ 5C induces MC degranulation via MRGPRX2.…”
Section: Discussionmentioning
confidence: 79%
“…We previously showed that PTx inhibits MC degranulation in response to HDP human b-defensin 3 without affecting Ca 2+ mobilization (19). We therefore tested the effect of PTx on degranulation and Ca 2+ mobilization to the well-established MRGPRX2 agonists compound 48/80 and AG-30/5C.…”
Section: Ptx Inhibits Ag-30/5c-induced MC Degranulation But Not Ca 2+mentioning
confidence: 99%
See 1 more Smart Citation
“…Host defense peptides (HDPs) also are an important part of innate immunity, which are the barriers for preventing invasion of pathogens [44]. This process is derived from HDPs regulating in ammatory cytokines and responses via some signaling pathways, such as Toll-like receptors 4, mitogen-activated protein kinase and nuclear factor-kappa B signaling pathways [45][46][47][48]. And the HBD-2 mRNA expression in pulmonary epithelial cells could be induced by lentinan in a concentration-and time-dependent manner [49].…”
Section: Discussionmentioning
confidence: 99%